ON THE VALIDITY AND SIGNIFICANCE OF NUMMULITES STAMINEUS NUTTALL IN THE PERSPECTIVE OF NUMMULITES DISCORBINUS (SCHLOTHEIM) AND NUMMULITES BEAUMONTI D'ARCHIAC AND HAIME IN THE MIDDLE EOCENE OF CAMBAY BASIN, INDIA (Rivista italiana di Paleontologia e Stratigrafia, 2005)
The incompletely described and hitherto controversial Nummulites stamineus Nuttall has been re-described from the Cambay Basin, India as a taxonomically valid species. Its distinctive characters include irregular septal filaments, rudimentary transverse trabecules and irregularity in the spire with increased thickness of whorl wall at the middle or late part, a few thick spiral canals and curved chamber top. Closely resembling Nummulites discorbinus and Nummulites beaumonti differ in the above characters, in the ratio of diameter to thickness of test, number of septal filaments and character of transverse trabecules. In true equatorial sections the three forms mutually differ in the size ratio of protoconch to deuteroconch, height to length of chamber, whorl height to chamber height and whorl height to thickness of whorl wall, and also in the number of whorls, number of chambers in specified whorl and height of foramina. The three species, moreover, differ in stratigraphic range in the Cambay Basin sequence. Consequently, the earlier treatments of N. stamineus as synonym of N. discorbinus or N. beaumonti stand invalid. The re-evaluation increases its stratigraphic significance in the upper Middle Eocene sequence and suggests wide biogeographic range in the Tethyan-Mediterranean Province.